An updated evaluation of serum sHER2, CA15.3, and CEA levels as biomarkers for the response of patients with metastatic breast cancer to trastuzumab-based therapies. - Alexandre Perrier; Pierre-Yves Boelle; Yves Chrétien; Joseph Gligorov; Jean-Pierre Lotz; Didier Brault; Eva Comperat; Guillaume Lefèvre; Mathieu Boissan (PLoS ONE, 2020)
Background The transmembrane receptor tyrosine kinase HER2 is overexpressed in approximately 15% of breast tumors and correlates with poor clinical prognosis. Several treatments that target HER2 are approved for treatment of HER2-positive metastatic breast cancer. The serum biomarkers most widely used to monitor anti-HER2 therapies in patients with HER2-positive metastatic breast cancer currently are CA15.3 and CEA. Nevertheless, their clinical utility in patients with breast cancer remains a subject of discussion and controversy; thus, additional markers may prove useful in monitoring the therapeutic responses of these patients. The extracellular domain of HER2 can be shed by proteolytic cleavage into the circulation and this shed form, sHER2, is reported to be augmented during metastasis of HER2-positive breast tumors. Here, we studied the clinical usefulness of sHER2, CA15.3, and CEA for monitoring treatment for breast cancer. Methods We measured prospectively pretreatment and post-treatment serum levels (day 1, 30, 60 and 90) of these three biomarkers in 47 HER2-positive, metastatic breast cancer patients treated with trastuzumab in combination with paclitaxel. Evaluation of the disease was performed according to the Response Evaluation Criteria in Solid Tumor (RECIST) at day 90. Results Patients with progressive disease at day 90 had smaller relative changes between day 1 and day 30 than those with complete, partial or stable responses at day 90: -9% versus -38% for sHER2 (P = 0.02), +23% versus -17% for CA15.3 (P = 0.005) and +29% versus -26% for CEA (P = 0.02). Patients with progressive disease at day 90 were less likely than the other patients to have a relative decrease of > 20% in their biomarker levels at day 30: 6% vs 33% for sHER2 (P = 0.03), 0% vs 27% for CA15.3 (P = 0.03), 4% vs 29% for CEA (P = 0.04). No patient with progressive disease at day 90 had > 20% reduction of the average combined biomarker levels at day 30 whereas 63% of the other patients had (P = 0.003). Moreover, when we analyzed a > 10% reduction of the average biomarker levels no patient with progressive disease at day 90 had a decrease > 10% at day 30 whereas 78% of other patients had (P<0.001, Se = 100%, Sp = 78%). Conclusion We show that regular measurement of sHER2, CA15.3, and CEA levels is useful for predicting the therapeutic response and for monitoring HER2-targeted therapy in patients with HER2-positive metastatic breast cancer. The average decrease of the three biomarkers with a threshold of > 10% appears to be the best parameter to distinguish patients who go on to have progressive disease from those who will have a complete, partial or stable response.